2020
DOI: 10.5430/ijhe.v9n5p84
|View full text |Cite
|
Sign up to set email alerts
|

A UTAUT Evaluation of WhatsApp as a Tool for Lecture Delivery During the COVID-19 Lockdown at a Zimbabwean University

Abstract: Focusing through the lens of the (COVID-19) lockdown which was enforced on the 30th of March 2020, it became apparent that students from rural resource-constrained educational institutions had to adapt to sustainable online learning platforms from traditional content delivery. WhatsApp a social networking app, but due to its low data consumption, it became a de-facto teaching and learning tool for Lupane State University (LSU) students in Zimbabwe. Prior studies have focused on the use of WhatsApp as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 26 publications
2
34
0
10
Order By: Relevance
“…Walan (2020) also observed that different technology tools promote variations in teaching. Studies have showed that WhatsApp support collaborative learning where information is shared among students (in line with the social cognitive theory of learning), hence, increased access to educational resources regardless of distance (Rambe & Chipunza, 2013;Maphosa, Dube & Jita, 2020). Furthermore, WhatsApp provides a cheaper learning platform for students in poor communities.…”
Section: Introductionmentioning
confidence: 80%
“…Walan (2020) also observed that different technology tools promote variations in teaching. Studies have showed that WhatsApp support collaborative learning where information is shared among students (in line with the social cognitive theory of learning), hence, increased access to educational resources regardless of distance (Rambe & Chipunza, 2013;Maphosa, Dube & Jita, 2020). Furthermore, WhatsApp provides a cheaper learning platform for students in poor communities.…”
Section: Introductionmentioning
confidence: 80%
“…Published studies have confirmed the effectiveness of the UTAUT model in investigating the students' acceptance of e-learning. For example, the acceptance and preparedness of students for e-learning in northeastern Thailand [31], a study of e-learning acceptance in postgraduate program at Universitas Negeri Makassar, Indonesia [32], e-learning acceptance level among accounting lecturers in the universities in Padang, Indonesia [33], factors that influence the intent of teachers in higher education to use e-learning in hybrid environments [34], and the evaluation on WhatsApp as a tool for learning during COVID-19 at a Zimbabwean University [35]. However, few if any studies have considered Malaysian post graduate students' behavioural intention to use online learning during the pandemic.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…If the participants expect online learning to perform excellently during COVID-19, they are more likely to use online learning. Past studies [31,35,39] claimed that effort expectancy would affect students' behavioural intention. Therefore, it was considered as the participants' perceived effortless use of online learning, which might affect their intention to have online learning class.…”
Section: Effort Expectancymentioning
confidence: 99%
See 1 more Smart Citation
“…Educational institutions have taken important steps towards digitalization by making a great effort to improve the telecommunications infrastructure and electronic administration [8][9][10]. Nowadays it is almost inconceivable to teach without technology, or without reference to methodologies such as gamification, inverted classrooms or bringing your own device [11][12][13], which can contribute to create new scenarios that facilitate and promote different processes within the classroom, and that connect and help transfer knowledge to the outside world [1,14,15].…”
Section: Introductionmentioning
confidence: 99%